ANALISIS PENGARUH FDR, PEMBIAYAAN MURABAHAH, DAN NPF TERHADAP PROFITABILITAS (ROA) PADA BANK UMUM SYARIAH (Studi Empiris Bank Umum Syariah di Indonesia Periode 2017-2020) - M. Ihsan Atthaariq; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of Finance to Deposit Ratio, murabahah financing, and Non Performing financing on the profitability (ROA) of Islamic Commercial Banks in Indonesia (case study of Islamic Commercial Banks in Indonesia in 2017-2020). The dependent variable used in this study is Return On Assets, while the independent variables of this study are Finance to deposit ratio, murabaha financing, and non-Performing Finance.The sample used in this study is Islamic Commercial Banks in Indonesia registered with the financial services authority (OJK) in 2017-2020 with predetermined criteria or samples taken using purposive sampling. The method of analysis in this study using panel data regression analysis.The results of this study indicate that there is a negative and significant effect of FDR, a positive and insignificant effect of murabahah financing, as well as a negative and significant effect of NPF on ROA of Islamic commercial banks in Indonesia in 2017-2020.